Emotionally Unavailable Parenting and Alexithymia: The Mediating Role of Attachment Insecurity - Sharma, Neha; Yildiz, Emre (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore whether attachment insecurity mediates the relationship between emotionally unavailable parenting and alexithymia in young adults.Methods and Materials: The study utilized a descriptive correlational design with a sample of 414 Turkish university students, determined based on the Krejcie and Morgan sample size table. Participants were selected through convenience sampling and completed three standardized self-report instruments: the Parental Bonding Instrument (PBI) to assess emotionally unavailable parenting, the Experiences in Close Relationships–Revised (ECR-R) to evaluate attachment insecurity, and the Toronto Alexithymia Scale-20 (TAS-20) to measure alexithymia. Data were analyzed using SPSS version 27 for descriptive and Pearson correlation analyses, while Structural Equation Modeling (SEM) was performed using AMOS version 21 to test the hypothesized mediational model. Model fit was evaluated using multiple fit indices.Findings: Results indicated moderate to high levels of emotionally unavailable parenting (M = 56.42, SD = 8.37), attachment insecurity (M = 82.15, SD = 10.92), and alexithymia (M = 61.78, SD = 9.45). Pearson correlations revealed significant positive relationships among all variables: emotionally unavailable parenting and attachment insecurity (r = .58, p < .001), emotionally unavailable parenting and alexithymia (r = .53, p < .001), and attachment insecurity and alexithymia (r = .61, p < .001). SEM confirmed that attachment insecurity significantly mediated the relationship between emotionally unavailable parenting and alexithymia, with strong model fit indices (χ²/df = 2.12, CFI = 0.96, RMSEA = 0.048).Conclusion: The findings highlight the pivotal role of attachment insecurity in linking emotionally unavailable parenting to alexithymia. These results emphasize the importance of enhancing emotional responsiveness in parenting to support healthier emotional development and attachment in young adults.